Pengembangan Media Flash Card Baca Kata Berbasis Ispring Suite Dalam Meningkatkan Literasi Anak Berusia 5-6 Tahun Di Taman Kanak-Kanak Islam Terpadu Sholahuddin 1 Bogor - Fitriani, Elly; Waspodo, Muktiono; Gatot, Masitowati (EDUCATE : Jurnal Teknologi Pendidikan, 2023)
This study aims to analyze: 1) The process of developing word reading flash card media based on the ispring suite in improving the literacy of children aged 5-6 years at the Sholahuddin 1 Integrated Islamic Kindergarten, Bogor, 2) Feasibility.development of flash card media for reading words based on the ispring suite in improving the literacy of children aged 5-6 years at the Integrated Islamic Kindergarten Sholahuddin 1 Bogor, 3) The effectiveness of developing flash card media for reading words based on ispring suitein improving the literacy of children aged 5-6 years at the Integrated Islamic Kindergarten Sholahuddin 1 Bogor. This research method is development research or also called Research and Development (R&D). By using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subjects in this study were students of TKIT Sholahuddin 1 Bogor. The results shown are the assessment of the feasibility of multimedia by material experts obtaining a score of 92% (very good). .the feasibility assessment by media experts got a score of 90.5% (very good), the feasibility assessment by the instructional design expert got a score of 95% (very good), and the feasibility assessment by linguists got 92% (very good). .based on the feasibility assessment of the experts above, this ispring suite based word reading flash card is considered very feasible to use. .The response of students of TKIT Sholahuddin 1 Bogor with the presence of flash card media for reading words based on the ispring suite on the word reading flash card application for the feasibility of the material in the individual trial was categorized as very good with an average score of 93%, in the 2 trialthe small group, showed an average score of 90% which was categorized as very good, and in the large group trial, it showed an average score of 96%. The feasibility of the learning design in the individual trial was categorized as good with an average score of 80%, in the small group trial, it showed an average score of 86.7% which was categorized as very good, and in the field trial it was categorized as good with .an average score of 84%.The feasibility of learning media in individual trials is categorized as very good with an average score of 86.7%, in small group trials it is categorized as very good with an average score of 86.7%, and in field trials with a very good categorywith an average score of 90%.The feasibility of learning media in individual trials is categorized as very good with an average score of 86.7%, in small group trials it is categorized as very good with an average score of 86.7%, and in field trials it is categorized as very goodwith an average score of 90%.The language feasibility in the field trial was categorized as very feasible with an average score of 93%, in the small group trial the very appropriate category with an average score of 90%, and in the field test with a very feasible category with a score of .an average of 96%.the response of students of TKIT Sholahuddin 1 Bogor in using flash card media, read words before using media or during the pre-test, an average score of 44.3% (not yet developed) and after using flash card media read words got a score.an average of 79.6% (developed as expected). The learning outcomes of 3 respondents are in the very high category with an N-Gain value of 1.4 and the other 4 respondents are in a good category with an N-Gain value of 0.9. There is no low score for respondents after using flash card media to read words. .range of N-Gain g values > 0.7 with High interpretation.so it can be concluded that the development of flash card media for reading words based on the ispring suite which is applied to students at TKIT Sholahuddin 1 Bogor is very feasible and very good in an effort to improve literacy in introducing early literacywhich is more significant in children aged 5-6 years.